Modos de ser criança no Quilombo Mato do Tição Joaboticatubas - MG - Patricia Maria de Souza Santana (2015)
This study seeks to understand the ways of being a kid in the Quilombo Mato do Tição, in JaboticatubasMG. Through participant observation, photographic records, drawings produced by the children, interviews and others methodological resources, we observe, talked and we interact with the children in their daily lives: in the celebrations, on the kid games, in association with the older, in the expressions of religiosity and in the relations with the environment in which they live. Starting from the understanding that children are social actors, producers of culture and that they possessing specific knowledge, we describe the different possibilities of learning in which children are inserted; analyze how they fit in this context where the traditional knowledge and the very culture of the Mato do Tição is being learned and re-signified by a new generation that has the opportunity to live and hang out in a place marked by a diversity of experiences, worldviews and ancestors values lived and shared by the group. The extensive festive calendar, the circulation in the various spaces of the quilombo and its surroundings, as well as participation in projects and workshops conducted in the community, allows the children a unique way of living their childhood developing and elaborating their identities as quilombolas children, reaffirming their membership in the group and being children with much playfulness and intensity.